The Importance Of Dialectological Knowledge For Future Teachers Of Foreign Languages - Kabulova Zulfiya Xojabayevna (Euro Asian Journal Publishing, 2024)
This article is devoted to the study of the professional competence of a future foreign language teacher using contextual context. The article analyzes key aspects of the professional competence of future foreign language teachers, the dialectological advantage of contextual influence and its role in the competence of future teachers. (50 ta so‘zdan kam bo‘lmasligi lozim)
Keywords: Dialect; education; speech